The Effectiveness of Citizen Journalism in Oversight of Public Services (Study at the South Sumatra Representative of the Ombudsman of the Republic of Indonesia) - Muhammad Budi; Amin Sihabudin (Program Studi Jurnalistik, Universitas Islam Negeri Raden Fatah Palembang, 2023)
This tesis is entitled